Analisis Sektor Potensial dan Strategi Pengembangan Perekonomian di Kabupaten Indragiri Hulu - Fahrur Roziqul Mirza; Muhammad Hidayat; Ranti Darwin (Akuntansi & Ekonomika, 2019)
The purpose of this study is to find out the potential sectors and economic development strategies in Indragiri Hulu Regency. The use of secondary data from the publication of the Central Statistics Agency of Indragiri Hulu Regency and Riau Province in the form of time series data from the Gross Regional Domestic Product in 2013-2017. The analysis tools used are: 1) Location Quotient Analysis (LQ) is used to determine the base and non-base sectors in the economy; 2) Shift Share Analysis is used to determine changes and shifts in the economic structure; 3) Klassen's typology is used to classify the structure of growth and the level of development; 4) ICOR analysis is used to find out how much investment needs. The results of the analysis by sector based on the four analysis tools show that the sector which is a potential sector and needs to be developed in Indragiri Hulu Regency is the sector of providing accommodation and food and drink, the real estate sector and the education service sector based on labor-intensive investment.